Answer

Verified

429.9k+ views

**Hint:**First, multiply and divide by the conjugate of the denominator to remove the imaginary part from the denominator and simplify it. After that find the modulus of z by the formula $\left| z \right| = \sqrt {{a^2} + {b^2}} $. Then, find the argument of z by ${\tan ^{ - 1}}\left( {\dfrac{y}{x}} \right)$.

**Complete step by step answer:**

Given, $z = \dfrac{{1 - 2i}}{{1 + 3i}}$

Multiply and divide z with the conjugate of the denominator,

$\Rightarrow z = \dfrac{{1 - 2i}}{{1 + 3i}} \times \dfrac{{1 - 3i}}{{1 - 3i}}$

Multiply the terms on the right to get real numbers in the denominator,

$\Rightarrow z = \dfrac{{1 + 6{i^2} - 2i - 3i}}{{1 - 9{i^2}}}$

As we know ${i^2} = - 1$, substitute the value in the equation,

$\Rightarrow z = \dfrac{{1 + 6\left( { - 1} \right) - 2i - 3i}}{{1 - 9\left( { - 1} \right)}}$

Open the brackets and add the like terms,

$\Rightarrow z = \dfrac{{ - 5 - 5i}}{{10}}$

Separate the real part and imaginary parts,

$\Rightarrow z = - \dfrac{5}{{10}} - i\dfrac{5}{{10}}$

Cancel out the common factors,

$\Rightarrow z = - \dfrac{1}{2} - \dfrac{1}{2}i$

The formula of modulus is,

$\Rightarrow \left| z \right| = \sqrt {{a^2} + {b^2}} $

Here $a = - \dfrac{1}{2}$ and $b = - \dfrac{1}{2}$. Then,

$\Rightarrow \left| z \right| = \sqrt {{{\left( { - \dfrac{1}{2}} \right)}^2} + {{\left( { - \dfrac{1}{2}} \right)}^2}} $

Square the terms in the bracket,

$\Rightarrow \left| z \right| = \sqrt {\dfrac{1}{4} + \dfrac{1}{4}} $

Since the denominator is the same. So, add the numerator,

$\Rightarrow \left| z \right| = \sqrt {\dfrac{2}{4}} $

Cancel out the common factors from the numerator and denominator,

$\Rightarrow \left| z \right| = \dfrac{1}{{\sqrt 2 }}$

Now, $\tan \alpha = \left| {\dfrac{b}{a}} \right|$. Then,

$\Rightarrow \tan \alpha = \left| {\dfrac{{ - \dfrac{1}{2}}}{{ - \dfrac{1}{2}}}} \right|$

Cancel out the common factor,

$\Rightarrow \tan \alpha = 1$

Take ${\tan ^{ - 1}}$ on both sides,

$

\alpha = {\tan ^{ - 1}}1 \\

= \dfrac{\pi }{4} \\

$

As both of the real part and the imaginary part of the complex number is negative. The number will lie in 3rd quadrant. Then,

$\Rightarrow \arg \left( z \right) = \pi + \alpha $

Substitute the value of $\alpha $,

$\Rightarrow \arg \left( z \right) = \pi + \dfrac{\pi }{4}$

Add the terms on the right side,

$\Rightarrow \arg \left( z \right) = \dfrac{{5\pi }}{4}$

**Hence, the modulus is $\dfrac{1}{{\sqrt 2 }}$ and the argument is $\dfrac{{5\pi }}{4}$.**

**Note:**

The complex numbers are the field C of numbers of the form $x + iy$, where x and y are real numbers and i is the imaginary unit equal to the square root of -1. When a single letter z is used to denote a complex number. It is denoted as $z = x + iy$.

Recently Updated Pages

How many sigma and pi bonds are present in HCequiv class 11 chemistry CBSE

Mark and label the given geoinformation on the outline class 11 social science CBSE

When people say No pun intended what does that mea class 8 english CBSE

Name the states which share their boundary with Indias class 9 social science CBSE

Give an account of the Northern Plains of India class 9 social science CBSE

Change the following sentences into negative and interrogative class 10 english CBSE

Trending doubts

Difference between Prokaryotic cell and Eukaryotic class 11 biology CBSE

Fill the blanks with the suitable prepositions 1 The class 9 english CBSE

Differentiate between homogeneous and heterogeneous class 12 chemistry CBSE

Which are the Top 10 Largest Countries of the World?

10 examples of evaporation in daily life with explanations

Give 10 examples for herbs , shrubs , climbers , creepers

Change the following sentences into negative and interrogative class 10 english CBSE

Write a letter to the principal requesting him to grant class 10 english CBSE

Difference Between Plant Cell and Animal Cell